Desenvolvimento de experimentos usando o módulo EB-109 (motores e geradores) para a disciplina de controle linear - Rocha, Lucas Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
In this work the experiments that form the EB-109 Course (Motors and Generators) of DEGEM SYSTEMS are reviewed in order to employ it in the course of Electrical Engineering of the Campus of the FEG. Each experiment was repeated using the equipment present at the Campus and the problems related to the course were identified. In addition, the theoretical aspects involving the components of this board and a small theory related to process control are presented in a simple way. A new experiment that includes principles of the area of system identification and modeling is proposed as well. This new experiment uses the EB-109 board and computational simulators such as MatLab and Simulink. By means of the analyzes, it is pointed out that the EB-109 Course can be used in the course of Linear Control of electrical engineering Department of Guaratinguetá Campus, and that the proposed experiment presents satisfactory results and can be added to the EB-109 Course material.

Neste trabalho os experimentos que formam o Módulo EB-109 (Motores e Geradores) da DEGEM SYSTEMS são revisados com o intuito de utilizá-lo no curso de Engenharia Elétrica do Campus da FEG. Além disso, são apresentados de forma simples os aspectos teóricos que envolvem os componentes da placa do Módulo EB-109 e uma resumida teoria relacionada com controle de processos. Também, um novo experimento que compreende princípios da área de identificação e modelagem de sistemas é proposto. Esse novo experimento se utiliza da própria placa do EB-109 e de simuladores computacionais como o MatLab e o Simulink. Por meio das análises feitas, salienta-se que o Módulo EB-109 pode ser utilizado no curso de Controle Linear do Departamento de Engenharia Elétrica no Campus de Guaratinguetá, e o experimento proposto apresenta resultados satisfatórios, podendo ser acrescentado ao material do Módulo EB-109 como mais um experimento.
Development of experiments using the EB-109 module (motors and generators) for the linear control discipline
Keywords: Maquinas eletricas; Modelagem de processos; Identificação de sistemas; Circuitos eletrônicos; Electric machinery